Clinical pattern of psoriasis in patients seen at our private clinic, in Aden, Yemen - Bin Al-Zou, Amer Omer (Sirte Journal of Medical Sciences, 2023)
Background: Psoriasis is a chronic immune-mediated systemic disease that is influenced by genetic and environmental factors. Objective: To presents the demographic characteristics, and clinical variants of psoriatic patients. Materials and methods: Present work was a retrospective and observational study, conducted in patients of a private clinic of dermatology, in Almansoora, Aden, Yemen. All patients who attended the clinic during the period January 2018 to December 2021 and were diagnosed as psoriasis patients were included in this study. Data were collected and entered in a computer, and analyzed by using SPSS version 17. Results: The study patients were 168. They were (57.1%) males and (42.9%) females, with a male-to-female ratio of 1.3:1. The age of the patients ranged between 10 to 58 years. The mean age of the patients was 38.2 ± 12.6 years. The age group 41 – 50 had the highest number of patients 54 (32.1%), followed by the age group 31 – 40 years 40 (23.8%) years. The mean duration since the onset of the disease is 6.1 ± 4.6 years. The most common psoriasis type was plaque psoriasis (vulgaris) (65.4%). Family history related to psoriasis was positive among (20.2%) patients. Diabetes mellitus and hypertriglyceridemia were found equally among the study patients, each one in (9.5%) and arterial hypertension was found in (7.2%) patients. The involvement of nails was observed in (31%) of patients and Koebner phenomena was found in (23.8%) of patients. Conclusion: Psoriasis is predominant in male patients, with a male-to-female ratio of 1.3:1, and the most common psoriasis type was plaque psoriasis.